Investigation of the Na Intercalation Mechanism into Nanosized V2O5/C Composite Cathode Material for Na-Ion Batteries - Ali, Ghulam; Lee, Ji-Hoon; Oh, Si Hyoung; Cho, Byung Won; Nam, Kyung-Wan; Chung, Kyung Yoon (American Chemical Society, 2016)
There is a significant interest to develop high-performance and cost-effective electrode materials for next-generation sodium ion batteries. Herein, we report a facile synthesis method for nanosized V2O5/C composite cathodes and their electrochemical performance as well as energy storage mechanism. The composite exhibits a discharge capacity of 255 mAh g(-1) at a current density of 0.05 C, which surpasses that of previously reported layered oxide materials. Furthermore, the electrode shows good rate capability; discharge capacity of 160 mAh g(-1) at a current density of 1 C. The reaction mechanism of V2O5 upon sodium insertion/extraction is investigated using ex situ X-ray diffraction (XRD) and synchrotron based near edge X-ray absorption fine structure (NEXAFS) spectroscopy. Ex situ XRD result of the fully discharged state reveals the appearance of NaV2O5 as a major phase with minor Na2V2O5 phase. Upon insertion of sodium into the array of parallel ladders of V2O5, it was confirmed that lattice parameter of c is increased by 9.09%, corresponding to the increase in the unit-cell volume of 9.2%. NEXAFS results suggest that the charge compensation during de/sodiation process accompanied by the reversible changes in the oxidation state of vanadium (V4+ <-> V5+).
Keywords: CORE-SHELL STRUCTURE; ABSORPTION-SPECTROSCOPY; VANADIUM-OXIDES; HIGH-CAPACITY; CARBON; NANOCOMPOSITE